P1251THROMBIN GENERATION ASSAY: A POTENTIAL TOOL TO STRATIFY THROMBOTIC RISK IN HEMODIALYSIS PATIENTS. (6th June 2020) - Kalikatzaros, Ileana; Radin, Massimo; Cecchi, Irene; Sciascia, Savino; Forneris, Giacomo; Pozzato, Marco; Sinico, Renato Alberto; Roccatello, Dario
Abstract: Background and Aims: Patients with Chronic Kidney Disease (CKD) in hemodialysis (HD) show both high thrombotic and hemorrhagic risks. However, routine laboratory techniques aimed to evaluate haemostasis, i.e. activated prothrombin time (PT) and activated partial thromboplastin time (aPTT), are not sensitive enough to detect mild hypocoagulable or hypercoagulable states in this population. Indeed, these methods evaluate the start-up phase of the coagulation, but omit the amplification stage in which an exponential increase of thrombin generation occurs. Thrombin generation assay (TGA) is a second-level global coagulative test able to evaluate thrombin generation and decay. So far the TGA has never been used for assessing thrombotic risk in HD patients. Method: This is a monocentric observational retrospective study conducted at San Giovanni Bosco Hospital and University of Turin, Italy. After chart-reviewing of all patients with CKD in HD, we enrolled: Group A) 100 Patients with CKD in HD, treated or not treated with warfarin Group B) 60 Patients treated with Warfarin with normal kidney function Group C) 60 Healthy Controls Results: Compared to healthy donor patients on hemodialysis that were not treated with warfarin had significantly lower tLag (mean tLag 8.2±3.4 vs. 9.7±2.9, p < 0.05), lower tPeak (mean tPeak 14.3±6 vs. 16.2±4.7, p < 0.05), lower Peak (mean Peak 151.8±77.4 vs. 209.2±103.8, p < 0.001) and lower AUC (mean AUC 1624.5±564.4 vs. 2023±489.2, p < 0.001) (Figure 1 ). Compared to controls with normal renal function treated with warfarin, HD patients treated with warfarin had higher tLag (mean tLag 10.5±3.3 vs. 8.3±2.1, p < 0.05), higher tPeak (mean tPeak 16.5±4.9 vs. 13±2.9, p < 0.05). Among HD patients who were not treated with warfarin, those with autoimmune conditions showed a pro-thrombotic TGA profile when compared to HD patients without autoimmune diseases, with significantly higher Peak (mean Peak 188.4±30 vs. 149.9±78.7, p < 0.05) and higher AUC (mean AUC 2066.9±138.2 vs. 1601.5±569, p < 0.001). Similarly, compared to patients without previous history of vascular events (59), patients with previous ischemic stroke or venous thrombosis (41), had significantly lower tLag (mean tLag 8±2.9 vs. 14.2±8.5, p < 0.001), lower tPeak (mean tPeak 14±5.6 vs. 21.7±12.3, p <0.05), higher Peak (mean Peak 154.9±76.8 vs. 71.83±49.2, p<0.05) and higher AUC (mean AUC 1653.7±548.7 vs. 863.4±501.4, p < 0.05). Of note, a significant positive relationship was detected between the International Normalized Ratio (INR) and both tLag (Pearson 0.46, p <0.001) and tPeak (Pearson 0.35, p <0.001). INR was inversely correlated to Peak (Pearson -0.47, p <0.001) and AUC (Pearson -0.61, p <0.001) (Figure 2 ). Conclusion: Identifying patients at high risk for cardiovascular diseases and thrombosis has an important impact on the management of patients with CKD in HD. In this study, we observed a prothrombotic TGA profile in patients with CKD in HD, especially those with autoimmune conditions or previous history of arterial events (especially ischemic stroke) or venous thrombosis. Prospective studies are needed to evaluate the possible clinical use of TGA as thrombotic risk stratification tool in HD patients.